Self-assessment for implementation of health promotion standards in hospitals, in medical education centers of Isfahan city - Atefeh Afshari; Ahmad-ali Eslami; Firoozeh Mostafavi; Elham Moazam; Mojtaba Golzari; Reza Etminani (Iranian Association of Health Education and Health Promotion, 2020)
Background and Objective: The World Health Organization encourages hospitals to implement the health promoting hospital plan to improve health service quality. The aim of this study was to self-assessment status of health promotion in hospitals and identify existing strengths and gaps. Materials and Methods: This study is a descriptive cross-sectional survey in which 9 educational hospitals were selected through census sampling. Health promotion self-assessment tools were used for the data collection. Data were analyzed using SPSS software and descriptive statistics. Results: In most hospitals, the status were good regarding the health promoting policy in the hospitalchr('39')s mission, the availability of information to other patient organizations, providing information on high-risk diseases, recording patient information and follow-up training to patients and families in outpatient counseling, referral or during discharge. But the status were poor in terms of policies for participating in Health Promoting Hospitals Network, allocating specific funding for these services, revising guidelines for evaluating health promotion needs of patients, training new staff on hospital health promotion policies, implementing staff smoking cessation programs, Staff awareness on the organizationchr('39')s health promotion policy, a written plan to work with partners, and a specific process for exchanging patient information between organizations to continue patient care. Other standards evaluated average in most hospitals. Conclusion: The average evaluation of most elements of standards indicates the unorganized implementation of some health promotion activities in hospitals. It is essential to organize and reinforce existing on-going activities, regular self-assessment of health promotion activities, and design interventions based on self-assessment results.